Quality improvement time-saving intervention to increase use of a clinical decision support tool to reduce low-value diagnostic imaging in a safety net health system. Issue 1 (12th February 2021) - Lee, Bryanna; Mafi, John; Patel, Maitraya K; Sorensen, Andrea; Vangala, Sitaram; Wei, Eric; Sarkisian, Catherine
Abstract : Importance: Electronic health record (EHR) clinical decision support (CDS) tools can provide evidence-based feedback at the point of care to reduce low-value imaging. Success of these tools has been limited partly due to lack of engagement by busy clinicians. Objective: Measure the impact of a time-saving quality improvement intervention to increase engagement with a CDS tool for low back pain imaging ordering. Design, setting and participants: We conducted a quasi-experimental difference-in-differences analysis at (BLINDED), examining back pain imaging orders from 29 May 2015 to 07 January 2016. The intervention site was (BLINDED) Emergency Medicine/Urgent Care Center (n=5736) and control sites included all other (BLINDED) hospitals and clinics (n=1621). In May 2015, the Department of Health Services installed a CDS tool that triggered a survey when clinicians ordered an imaging test, generating an 'appropriateness score' based on the American College of Radiology guidelines. Clinicians often bypassed the tool, resulting in 'unscored' tests. Intervention: To increase clinician engagement with the tool and decrease the rate of unscored imaging tests, a new policy was implemented at the intervention site on 15 August 2015. If clinicians completed the CDS survey and scored an appropriateness score >3, they could forego a previously mandatory telephone call for pre-imaging utilisation review with the radiology department. Main outcomes and measures: We used EHR data to measure pre–post-intervention differences in: (1) percentage of unscored tests and (2) percentage of tests with high appropriateness scores (>7). Results: Percentage of unscored tests decreased from 69.4% to 10.4% at the intervention site and from 50.6% to 34.8% at the control sites (between-group difference: −23.3%, p<0.001). Percentage of high scoring tests increased from 26.5% to 75.0% at the intervention site and from 17.2% to 22.7% at the control sites (between-group difference: 19%, p<0.001). Conclusion: Workflow time-saving interventions may increase physician engagement with CDS tools and have potential to improve practice patterns.